2020
DOI: 10.1016/j.artmed.2020.101880
|View full text |Cite
|
Sign up to set email alerts
|

Breast ultrasound region of interest detection and lesion localisation

Abstract: In current breast ultrasound Computer Aided Diagnosis systems, the radiologist preselects a region of interest (ROI) as an input for computerized breast ultrasound image analysis. This task is time consuming and there is inconsistency among human experts. Researchers attempting to automate the process of obtaining the ROIs have been relying on image processing and conventional machine learning methods. We propose the use of a deep learning method for breast ultrasound ROI detection and lesion localisation. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 28 publications
2
60
0
Order By: Relevance
“…The use of ultrasound imaging to detect breast lesions is considered to be an important step in a computer-aided diagnosis system. 107 ABUS can combine deep learning and convolutional neural network (CNN) to distinguish benign and malignant breast masses. 108 Vakanski et al 109 proposed a breast tumor segmentation method in ultrasound images that combines visual saliency and deep learning models.…”
Section: Image Guided Positioning Technologymentioning
confidence: 99%
“…The use of ultrasound imaging to detect breast lesions is considered to be an important step in a computer-aided diagnosis system. 107 ABUS can combine deep learning and convolutional neural network (CNN) to distinguish benign and malignant breast masses. 108 Vakanski et al 109 proposed a breast tumor segmentation method in ultrasound images that combines visual saliency and deep learning models.…”
Section: Image Guided Positioning Technologymentioning
confidence: 99%
“…Breast lesion segmentation remains an unsolved problem as a result of these difficulties [ 15 , 16 , 17 ]. Existing studies lack vigor, intensity inhomogeneity, artifact removal, and precise lesion segmentation [ 15 , 16 , 18 , 19 ]. Because of the deep convolutional process, which extracts rich feature vectors, deep learning-based approaches for semantic segmentation and classification have gained popularity [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used in target detection and recognition in natural images (9)(10)(11)(12) and also shows high efficiency in clinical applications. It has been used in the region of interest detection and lesion localization on medical images, such as ultrasound images, X-ray images, and CT images (13)(14)(15). Sa et al (13) applied a fine-tuned Faster-RCNN trained on natural images to identify landmark points in lateral lumbar X-ray images and demonstrated that using very small annotated clinical datasets can also achieve great accuracy.…”
Section: Introductionmentioning
confidence: 99%